Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1039/c2cp23755e
|View full text |Cite
|
Sign up to set email alerts
|

A density functional theory study of hydrogen dissociation and diffusion at the perimeter sites of Au/TiO2

Abstract: Reactivity of supported gold catalysts is a hot topic in catalysis for many years. This communication reports an investigation on the dissociation of molecular hydrogen at the perimeter sites of Au/TiO(2) and the spillover of hydrogen atoms from the gold to the support using density functional theory calculations. It is found that the heterolytic dissociation is favoured in comparison with homolytic dissociation of molecular hydrogen at the perimeter sites. However, the surface oxygen of the rutile TiO(2)(110)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
52
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 50 publications
11
52
0
1
Order By: Relevance
“…Our recent study on H 2 oxidation found that, in the presence of Ti−OH, the fastest H 2 activation pathway was via heterolytic activation at the MSI, resulting in a formal hydride developing on the Au and a proton migrating to the support . Similar heterolytic H 2 activation mechanisms have been proposed previously to explain Haruta's H 2 /D 2 equilibration work, and Sun et al .’s DFT calculations …”
Section: Discussionsupporting
confidence: 84%
“…Our recent study on H 2 oxidation found that, in the presence of Ti−OH, the fastest H 2 activation pathway was via heterolytic activation at the MSI, resulting in a formal hydride developing on the Au and a proton migrating to the support . Similar heterolytic H 2 activation mechanisms have been proposed previously to explain Haruta's H 2 /D 2 equilibration work, and Sun et al .’s DFT calculations …”
Section: Discussionsupporting
confidence: 84%
“…The selectivity of ethylene formation can be calculated by comparing the hydrogenation barriers and the desorption barriers of ethylene. The latter values are estimated with the absolute values of ethylene adsorption energy, as reported previously [24,[49][50][51][52]. The adsorption energies and hydrogenation barriers of ethylene over Pd(100), Pd(100)-0.25C and Pd(100)-0.50C surfaces are listed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…It seems that the higher hydrogenation activity of Au/TiO 2 is due to specific metal-support interaction. Fujitani [36] study [37] proved this phenomenon. Yong revealed the favored heterolytic dissociation of H 2 with E a 00.37 eV at the perimeter sites of Au/TiO 2 , where Au atom and a nearby surface O (s) 2− were involved.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of this process, oxygen atoms near the perimeter were passivated. Further H 2 dissociation occurred on pure gold atoms via a homolytic mode with E a 00.64 eV [37].…”
Section: Resultsmentioning
confidence: 99%